Evaluation of Co-Relation between BCLC Stage of HCC and Alpha-Fetoprotein Levels - Aqsa Hamayun, Syed Anees Ahmed Gardezi, Najmusaqib Khan Niazi, Syed Haider Tirmizi, Iffat Rafique, Rabia Sadiq, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: One of the leading cancers worldwide is the hepatocellular carcinoma, ranked as the 6th most common cancers. Aim: To evaluate the co-relation between BCLC staging of HCC and alpha fetoprotein levels. Study design: Cross-sectional study. Methodology: Patients (n=90) of either gender irrespective of age who were diagnosed with hepatocellular carcinoma were included into the study. Clinical examination was performed and findings were noted. Eastern cooperative oncology group ECOG scoring system was used to identify the functional performance status of the patients. Hepatocellular carcinoma staging was done using the BCLC scoring system. Complete blood counts, Liver function tests (LFTS), INR, alpha fetoprotein levels, viral serology for hepatits and ultrasonography of abdomen were performed for all the patients. Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: Mean AFP levels were 400.7±305.4 IU/ml with a range of 8.50- 1015 IU/ml. 3(3.3%) patients were in BCLC stage 0, 23(25.6%) were in stage A, 33(36.7%) in stage B, 15(16.7%) in stage C and 16 (17.8%) in stage D. Results showed significant positive correlation between BCLC staging and AFP levels (r=o.834, p=0.001). Conclusion: It was concluded that Hep C followed by Hep B was the main cause of HCC. AFP has a significant diagnostic and prognostic value with positive co-relation with HCC. Keywords: Alpha-Fetoprotein, BCLC Staging, HCC and Liver Disease.